2019
DOI: 10.1111/ijd.14739
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgery and adjuvant treatment on the outcome of extraocular sebaceous carcinoma: a systematic review and individual patient's data analysis of 206 cases

Abstract: Background Extraocular sebaceous carcinoma (EOSC) is an aggressive malignancy of the sebaceous gland. Surgery is considered the cornerstone of treatment, but there is lack of clarity about extent and adjuvant treatment. Methods We conducted a systematic review and analysis of individual patient data of all published cases of EOSC to look into demography, pattern of care, importance of type of surgery, and other adjuvant treatment and survival outcome. A search of PubMed and Google Scholar was done with the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…5,7,10,13 For extraocular SAC, wide excision was the surgery of choice. 18 For nonextraocular SAC, Mohs surgery could bring at least similar disease-specific and overall survival to wide excision. [19][20][21] The authors observed that the gross excision (Mohs surgery included) independently indicated better prognosis for young and middle-aged SAC, although higher proportions of small tumors (#20 mm) were removed by gross excision rather than by wide excision (84.4% vs 55.2%; p , .001).…”
Section: Discussionmentioning
confidence: 99%
“…5,7,10,13 For extraocular SAC, wide excision was the surgery of choice. 18 For nonextraocular SAC, Mohs surgery could bring at least similar disease-specific and overall survival to wide excision. [19][20][21] The authors observed that the gross excision (Mohs surgery included) independently indicated better prognosis for young and middle-aged SAC, although higher proportions of small tumors (#20 mm) were removed by gross excision rather than by wide excision (84.4% vs 55.2%; p , .001).…”
Section: Discussionmentioning
confidence: 99%
“…Different figures have been reported regarding its lymphatic involvement and metastasis rates. Lymphatic metastasis rates of 1.3-16% and non-lymph node metastasis rates of 0.4-10% have been reported (55,56). Due to these different rates, there are different attitudes regarding the use of sentinel lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of adjuvant radiotherapy is controversial, radiotherapy can be given after complete tumor resection either alone or in combination with chemotherapy (55). Primary radiotherapy alone is not recommended due to high recurrence rates (56,58,60). It can be used in patients who refuse surgery or cannot undergo surgery due to comorbidities, and there are also publications that recommend its postoperative use after resection (55).…”
Section: Discussionmentioning
confidence: 99%
“…45 Our results mirror those clinical studies that have shown that extraocular SC are only locally aggressive tumors with low mortality rate; however, some studies have shown that some tumors may have demonstrated regional nodal and even visceral metastases. 29,44,[46][47][48] In our experience, cases of extraocular SC follow an indolent clinical course after complete excision. This study has some important limitations: none of our extraocular SC underwent sentinel lymph node biopsy; also, its retrospective nature limits the long-term clinical data available for analysis.…”
Section: Sebaceousmentioning
confidence: 99%